The Difference in Knowledge Levels of Academic Students and Proffesional Student in Prevention of Healthcare Associated Infection) - Khansa Salsabila Wahyu Widyan Utami; Wantiyah Wantiyah; Purwandari Retno (Jurnal Berita Ilmu Keperawatan, 2022)
Among healthcare workers, nurses are the ones most exposed to patients since they are in contact 24h a day. Nurses lack of knowledge factors can lead to HAIs. Therefore, it’s important especially for nurses and nursing students to understand how to prevent HAIs. The aim of this study was to analyze the difference in knowledge levels of academic nursing students and professional nursing students in prevention. This study used descriptive design with comparative analysis. Total participant is 298 nursing students consisted of 196 academic nursing students and 102 professional nursing students were gathered with total sampling technique and statistic test used Mann Whitney. The results showed there aren’t a difference in knowledge level of the academic nursing students and professional nursing students, on the indicator of knowledge about HAIs (p= 0,619), on the indicator of knowledge about standard precautiom (p= 0,459), and there is a difference on the indicator of knowledge about hand hygiene (p= 0.001). Almost all respondents have good knowledge about HAIs. Knowledge of HAIs is very important to learn, with the aim that nursing students can avoid exposure to HAIs, and can apply HAIs prevention and control when practicing in healthcare settings